Genetics, Cognition, and Neurobiology of Schizotypal Personality: A Review of the Overlap with Schizophrenia - Ettinger, Ulrich; Meyhöfer, Inga; Steffens, Maria; Wagner, Michael; Koutsouleris, Nikolaos (Frontiers in Psychiatry, 2014)
Schizotypy refers to a set of temporally stable traits that are observed in the general population and that resemble the signs and symptoms of schizophrenia. Here, we review evidence from studies on genetics, cognition, perception, motor and oculomotor control, brain structure, brain function and psychopharmacology in schizotypy. We specifically focused on identifying areas of overlap between schizotypy and schizophrenia. Evidence was corroborated that significant overlap exists between the two, covering the behavioural, brain structural and functional as well molecular levels. In particular, several studies showed that individuals with high levels of schizotypal traits exhibit alterations in neurocognitive task performance and underlying brain function similar to the deficits seen in patients with schizophrenia. Studies of brain structure have shown both volume reductions and increases in schizotypy, pointing to schizophrenia-like deficits as well as possible protective or compensatory mechanisms. Experimental pharmacological studies have shown that high levels of schizotypy are associated with (i) enhanced dopaminergic response in striatum following administration of amphetamine and (ii) improvement of cognitive performance following administration of antipsychotic compounds. Together, this body of work suggests that schizotypy shows overlap with schizophrenia across multiple behavioural and neurobiological domains, suggesting that the study of schizotypal traits may be useful in improving our understanding of the aetiology of schizophrenia.